Inhaled nitric oxide dependency at the end of double‐lung transplantation: a boosted propensity score cohort analysis. (26th December 2018) - Fessler, Julien; Godement, Mathieu; Pirracchio, Romain; Marandon, Jean‐Yves; Thes, Jacques; Sage, Edouard; Roux, Antoine; Parquin, François; Cerf, Charles; Fischler, Marc; Le Guen, Morgan
Summary: Inhaled nitric oxide (iNO) is usually used during lung transplantation despite controversial postoperative benefits. Our group chose to administer iNO systematically during the procedure and stop at the end of surgery. This study aims to describe the features of patients who cannot be weaned from iNO, the reasons for this and its impact on postoperative outcomes. This is a monocentric cohort study comprised all consecutive patients who underwent double‐lung transplantation (DLT) between 1 January 2012 and 1 January 2016. The impact of iNO dependency on postoperative outcomes was estimated using a boosted inverse probability of treatment weighting estimator. A total of 9.8% of the 173 patients included in the study could not be weaned from iNO at end‐surgery stage. Body mass index (OR = 2.03, 95% CI = 1.14–3.29, P  = 0.02) and intraoperative extracorporeal membrane oxygenation (OR = 1.80, 95% CI = 1.02–2.72, P  = 0.04) were risk factors for iNO dependency In the weighted population, iNO dependency was associated with an increased prevalence of grade 3 primary graft dysfunction (adjusted RR = 4.20, 95% CI = 1.75–10.09, P  < 0.001) and decreased postoperative survival during the first 1500 days of follow‐up (adjusted HR = 5.0, 95% CI = 1.86–13.48, P  < 0.001). Inhaled nitric oxide dependency is an early marker of a poor prognosis following DLT.